PENGARUH LAYANAN INFORMASI TERHADAP SELF EFFICACY SISWA KELAS X MADRASAH ALIYAH DARUL HIKMAH PEKANBARU TAHUN AJARAN 2013/2014 - Liza Wati; Abu Asyari; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study, entitled "Effect of Self-Efficacy Against Information Services Class-X students of Madrasah Aliyah Darul Hikmah Pekanbaru Academic Year 2013/2014". The purpose of study: 1) To reveal the students self-efficacy before being given information services. 2) To reveal the students self-efficacy after the give information services. 3) To determine difference in self-efficacy of students before and after giving the service information. 4) To determine the effect of self-efficacy information service to students. The population in this study class-X of academic year 2013/2014. Sampling techniques; that probability sampling technique provides equal opportunity for every element to be elected as members of the population sample. Sampling using; simple random sampling method is decision-member sample of the population was randomly without regard to existing strata in the population. Design of study is "one group pretest-posttest design" first performed measurements of the time giving one-time questionnaire before and after the administration of the service. Analysis using statistical percentages, to distinguish the self-efficacy of students before and after the test information service using "t", obtained tgreather than ttable (-15,17>1.98) at the 5% error level. Thus H0 rejected and Ha accepted, it means that there is a significant difference to the students self-efficacy before and after information services class-X Madrasah Aliyah Darul Hikmah Pekanbaru Academic Year 2013/2014. The results of test product moment r=0.66 and coefficient determinant r2=0,43. Concluded that after execution of self-efficacy information service class-X Madrasah Aliyah Darul Hikmah rise of Pekanbaru.Key Words : Information Services, Self-Efficacy